Chambers Pocket Dictionary - Editors Higgleton, Elaine ; Sargant, Howard and Seaton, Anne (Edinburgh Chambers, 1998)
This edition of this dictionary offers in-depth coverage of scientific, technical and computer terms. It is designed for ease of use with 60,000 references and simple, immediately accessible
Keywords: English language